Effect of Malondialdehyde-Induced Oxidation Modification on Physicochemical Changes and Gel Characteristics of Duck Myofibrillar Proteins - Xueshen Zhu; Zhenghao Ma; Xinyu Zhang; Xuefang Huang; Junya Liu; Xinbo Zhuang (Gels, 2022)
This paper focuses on the effect of malondialdehyde-induced oxidative modification (MiOM) on the gel properties of duck myofibrillar proteins (DMPs). DMPs were first prepared and treated with oxidative modification at different concentrations of malondialdehyde (0, 0.5, 2.5, 5.0, and 10.0 mmol/L). The physicochemical changes (carbonyl content and free thiol content) and gel properties (gel whiteness, gel strength, water holding capacity, rheological properties, and microstructural properties) were then investigated. The results showed that the content of protein carbonyl content increased with increasing MDA oxidation (p < 0.05), while the free thiol content decreased significantly (p < 0.05). Meanwhile, there was a significant decrease in gel whiteness; the gel strength and water-holding capacity of protein gels increased significantly under a low oxidation concentration of MDA (0–5 mmol/L); however, the gel strength decreased under a high oxidation concentration (10 mmol/L) compared with other groups (0.5–5 mmol/L). The storage modulus and loss modulus of oxidized DMPs also increased with increasing concentrations at a low concentration of MDA (0–5 mmol/L); moreover, microstructural analysis confirmed that the gels oxidized at low concentrations (0.5–5 mmol/L) were more compact and homogeneous in terms of pore size compared to the high concentration or blank group. In conclusion, moderate oxidation of malondialdehyde was beneficial to improve the gel properties of duck; however, excessive oxidation was detrimental to the formation of dense structured gels.